Treatments of jute fibers aiming at improvement of fiber-phenolic matrix adhesion - Ilce Aiko Tanaka Razera (Polímeros, 2014)
Composites based on a thermoset phenolic matrix and jute fibers were prepared and characterized. The fibers were alternatively treated with ionized air or aqueous alkaline solution (mercerization) with the aim of introducing changes in the morphology, dispersive component of surface free energy, γS D (estimated by Inverse Gas Chromatography, IGC) and the acid/base character of their surfaces, shown by their ANs/DNs ratio (estimated by IGC), and their degree of crystallinity. The final objective was to investigate the influence of these modifications on the adhesion at the jute fiber/phenolic matrix interface in the composites. The untreated jute fiber showed 50% crystallinity, γS D=18 mJ m- 2 and ANs/DNs= 0.9 (amphoteric surface), tensile strength = 460 MPa and maximum elongation = 0.7%, while the respective composite had an impact strength of 72.6 J m- 1. The treatments positively modified the fibers and the adhesion at the interface was better in the composites reinforced with treated fibers than with untreated fibers. The best set of results was exhibited by the fiber treated with 10% NaOH [46% crystallinity, γS D = 26 J m- 2 (phenolic matrix γS D = 32 J m- 2), ANs/DNs = 1.8 (surface predominantly acidic, similar to phenolic matrix, ANs/DNs = 1.4), tensile strength approximately 900 MPa, maximum elongation = 2%, impact strength of respective composite approximately 95 J m- 1)]. The fibers treated for 5 h with ionized air exhibited favorable properties [(45% crystallinity, γS D = 27 J m- 2, ANs/DNs = 2.1 (acidic surface)] for further use as reinforcement of a phenolic matrix, but their partial degradation during the treatment decreased their tensile properties (395 MPa and 0.5% for tensile strength and maximum elongation, respectively) and their action as reinforcement (impact strength of the respective composite approximately 73 J m- 1).